Pengembangan Media Pembelajaran Pencak Silat Berbasis Video Compact Disc - Sudirman, Ridwan (IKIP PGRI Pontianak, 2024)
This study aims to develop a learning media for pencak silat based on instructional VCDs. The method used is the ADDIE model of research and development, with the following reasons: (1) it can be adapted to almost any product development context, including instructional VCDs, (2) the product can be continuously improved at each stage to produce better instructional materials, and (3) the development process is simple, systematic, and practical. Evaluation results show that the pencak silat instructional VCD received a 95% rating from subject matter experts and 80% from media experts, with categories of very good and good, respectively. A trial with students resulted in a 99% rating with a category of very good. It can be concluded that this pencak silat instructional VCD facilitates learning because it is equipped with video tutorials demonstrating the movements, making it easier and more practical for users to follow along.